Nutritional comparison between hydroponically grown leguminous and non-leguminous fodder to identify the adaptability and best harvesting time for sustainable hydroponic grass production - Kabir, Md Ahsanul; Hai Rakib, Md Rezaul; Amin, Md Ruhul; Hossain, SM Jahangir; Amanullah, Sardar Muhammad; Deb, Gautam Kumar; Das, Nani Gopal (Research in Agriculture Livestock and Fisheries, 2022)
Two types of fodder crops were evaluated in this study, maize (Zia maize) and black gram (BG) (Vigna mungo) and in maize, non-descriptive local maize (LM) and hybrid maize (HM) verity were used. LM was considered as control and changes of the nutritional composition according to the type of fodder (leguminous and non-leguminous) and the day was evaluated. For comparative nutritional analysis, dry matter (DM), crude protein (CP), ether extract (EE), crude fibre (CF), acid detergent fibre (ADF), neutral detergent fibre (NDF), and total ash were analyzed and the biomass yield was measured using weight balance and root and shoot length of experimental fodders. Results revealed that among three types of forages total DM was significantly (P<0.01) higher in HM and significantly (P<0.01) lower in BG. Considering total CP and NDF, it was significantly (P<0.01) higher in BG and HM than LM. The highest biomass yield and shoot length were observed in BG and the lowest biomass yield was observed in HM. Moreover, with the increment of days, all fodder sprouts DM% was constantly decreasing, however, CP% maintained the same level from day 1 to 5. Although from day 6 to 9, CP% increased moderately for HM and BG, CP% decreased slightly for LM. Therefore, farmer can use BG and HM for maximum utilization of nutrients and considering DM and CP% for LM day 6 was the best time for harvesting; however, for HM and BG, day 9 or more than 9 was the best time for harvesting. Res. Agric., Livest. Fish.8(3): 321-328, December 2021